Decreased expression of FOXF2 as new predictor of poor prognosis in stage I non-small cell lung cancer - Kong, Peng-Zhou (Oncotarget, 2016)
BACKGROUND: Forkhead box F2 (FOXF2) is relatively limited to the adult lung, but its contribution to non-small cell lung cancer (NSCLC) prognosis is unclear. RESULTS: FOXF2 mRNA levels in NSCLC were lower than that in paired normal lung tissues (P = 0.012). The FOXF2(low) patients had shorter survival time than the FOXF2(high) patients (P = 0.024) especially in stage I (P = 0.002), chemotherapy (P = 0.018) and < 60 age groups (P = 0.002). Lower FOXF2 mRNA levels could independently predict poorer survival for patients with NSCLC (HR = 2.384, 95% CI = 1.241–4.577; P = 0.009), especially in stage I (HR =4.367, 95% CI =1.599–11.925; P = 0.004). The two independent datasets confirmed our findings. METHODS: We examined FOXF2 mRNA levels in 84 primary NSCLC and 8 normal lung tissues using qRT-PCR. Rank-sum tests and chi-square tests were used to assess the differences among groups with various clinicopathological factors. Kaplan-Meier tests were used to compare survival status in patients with different FOXF2 mRNA levels. Cox proportional hazards regression model was used to evaluate the predictive value of FOXF2 mRNA level in NSCLC patients. Independent validation was performed using an independent dataset (98 samples) and an online survival analysis software Kaplan-Meier plotter (1928 samples). CONCLUSIONS: Our results demonstrated that decreased FOXF2 expression is an independent predictive factor for poor prognosis of patients with NSCLC, especially in stage I NSCLC.